Use of Umbilical Cord flap for Closure of Gastroschisis - Ferdous, Kazi Md Noor ul; Hasan, Md Samiul; Kabir, Kh Ahasanul; Zahid, Mirza Kamrul; Islam, M Kabirul; Hasanuzzaman, Md (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: Primary reduction of swollen oedematous viscera in gastroschisis is difficult, results abdominal compartment syndrome and associated with poor prognosis. Use of umbilical cord flap reduce intra-abdominal pressure and results batter outcome. Objective: This retrospective study was done to evaluate the outcome of gastroschisis patient in whom umbilical cord flap covering was given. Methods: Clinical records of the patients of gastroschisis were evaluated retrospectively during the period of July 2014 to June 2017, whom the abdominal wall defect ware covered with umbilical cord flap. After reduction of bowel into the abdomen as much as possible without pressure, the remaining eviscerated intestine is covered by the longitudinally split umbilical cord if the adequate length was available. Results: Total 108 neonates were admitted with gastroschisis. Out of them, in 27 neonates umbilical cord flap were used. In 16 cases, abdominal defect was healed completely. Eight patients developed ventral hernia required secondary repair operation when 1 year 6 months old. All 24 survived children were followed up for 6 months to 2 years 6 months. Mean follow up time was 1.7 ±1.3 years. Conclusion: Umbilical cord flap coverage could be a better technique in repair of gastroschisis with oedematous gut, where postoperative NICU facilities is limited. J Shaheed Suhrawardy Med Coll, June 2018, Vol.10(1); 47-50